In Vitro Toxicity Evaluation of Silver Nanoparticles on Entamoeba histolytica trophozoite - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
The protozoan parasite Entamoeba histolytica is a causative agent of amoebiasis, where it causes millions of cases of dysentery and liver abscess each year. Metronidazole is a drug of choice against amoebiasis. The drug is a choice because of its efficacy and low cost, but at the same time it causes several adverse side effects; therefore, it is important to find effective medications to treat amoebiasis without any complications or any side effects. The aim of this study is to evaluate the effectiveness of different concentrations (50, 75 and 100 µg/ml) of silver nanoparticle (AgNPs) against trophozoites stages of E. histolytica in vitro. The results showed a significant decrease (p ? 0.05) in numbers of trophozoites stages after treated with AgNPs and metronidazole when it was compared with the control. Likewise, a significant difference (p ? 0.05) was also observed between AgNPs groups and metronidazole drug, while it did not significantly differ between different concentrations of AgNPs. The mortality rate values of the E. histolytica trophozoites after 48h incubation with AgNPs at a concentration of 50, 75 and 100 ?g/ml, and metronidazole were 37.2%, 42.4%, 46.7% and 100%, respectively. The microscopic studies confirmed that AgNPs were effective enough to induce apoptosis. Based on our results, the anti-parasitic activity of AgNPs at different concentrations will reduce the mean number of E. histolytica trophozoites.